Regulation of T-independent B-cell responses by microRNA-146a - King, Jennifer K.; Tran, Tiffany M.; Paing, May H.; Yin, Yuxin; Jaiswal, Amit K.; Tso, Ching-Hsuan; Roy, Koushik; Casero, David; Rao, Dinesh S. (Frontiers in Immunology, 2022)
The microRNA, miR-146a, is a negative feedback regulator of the central immune transcription factor, nuclear factor kappa B (NFkB). MiR-146a plays important roles in the immune system, and miR-146a deficient mice show a complex phenotype with features of chronic inflammation and autoimmune disease. In this study, we examined the role of miR-146a in extrafollicular B-cell responses, finding that miR-146a suppresses cellular responses in vivo and in vitro. Gene expression profiling revealed that miR-146a-deficient B-cells showed upregulation of interferon pathway genes, including Traf6, a known miR-146a target. We next interrogated the role of TRAF6 in these B-cell responses, finding that TRAF6 is required for proliferation by genetic and pharmacologic inhibition. Together, our findings demonstrate a novel role for miR-146a and TRAF6 in the extrafollicular B-cell responses, which have recently been tied to autoimmune disease pathogenesis. Our work highlights the pathogenetic role of miR-146a and the potential of pharmacologic inhibition of TRAF6 in autoimmune diseases in which miR-146a is deregulated.